The Effects of Laparoscopic Sleeve Gastrectomy on Glucose Metabolism in Patients with a Body Mass Index below 35 kg/m² - Batman, Burçin (Sisli Etfal Hastan Tip Bul, 2020)
OBJECTIVES: The prevalence of obesity and its associated comorbidities are increasing all over the world. Laparoscopic sleeve gastrectomy has become the most common bariatric surgery in the world today, especially in the treatment of Type 2 diabetes mellitus, which is one of the effective surgical methods. The present study aims to investigate the effects on glucose metabolism in patients following laparoscopic sleeve gastrectomy. METHODS: In this study, the files of 174 patients who had laparoscopic sleeve gastrectomy with a body mass index between 30-35kg/m2 between March 2013 and September 2019 were analyzed retrospectively. Patients were evaluated by a multidisciplinary team in the preoperative period. Patients who met the criteria for laparoscopic sleeve gastrectomy were operated according to American Metabolic and Bariatric Surgeons criteria. Demographic data, body mass index, insulin, glycosylated hemoglobin (HbA1c), glucose, homeostasis model insulin resistance (HOMA-IR) values were recorded. The patients were followed up with visits to the outpatient clinic scheduled for 1-3-6 and 12 months postoperatively. RESULTS: The mean age of the 174 patients who underwent laparoscopic sleeve gastrectomy was 39.57±9.40, and the mean body mass index was 32.70±2.65. 149 patients (85.6%) were female. The mean hospital stay was 3.1±0.7 days. When glucose, HbA1c, HOMAR-IR and insulin values of the patients were examined, it was observed that the decrease was statistically significant at 12 months follow-up. There was a significant decrease in body mass index compared to the preoperative period. CONCLUSION: Laparoscopic sleeve gastrectomy is an effective surgery on glucose metabolism in patients with a body mass index of 30-35kg/m(2).